First language and proficiency level effects on English vowel perception by Iraqi learners of English in Malaysia - Al Abdely, Ammar Abdul-Wahab; Ilyana Jalaluddin,; Che An Abdul Ghani,; Yap, Ngee Thai (Penerbit Universiti Kebangsaan Malaysia, 2016)
Motivated by the assumptions that first language (L1) influence was found to be a very strong predictor of foreign accent degree in the pronunciation of second language learners and that increased experience in the second language (L2) may nurture improved recognition of the differences between the L1 and L2 segments, this study examines the effect of L1 and proficiency level on the perception of English monophthongs by Iraqi EFL learners. Iraqi learners of English who speak Baghdadi Arabic as their native language were recruited for the study. Their level of proficiency in English was measured with the Quick Placement Test (UCLES, 2001). Performance in the perception test revealed that Iraqi learners face different levels of difficulty in the perception of most monophthongs in English. The results showed prominent perceptual trends regardless of the learner's proficiency level for some vowels, suggesting strong L1 effect across all proficiency levels. The study also found that the perceptual abilities of EFL learners can be improved with more exposure to the L2. The errors made by Iraqi learners can be explained based on perceived similarity and distance between L2 and L1 vowel spaces.